Selection of recycled water electrochemical conditioning parameters for preparation of diamond-bearing kimberlite for froth separation - G. P. Dvoichenkova; V. V. Morozov; E. L. Chanturia; E. G. Kovalenko (Горные науки и технологии, 2021)
The main reason of decreasing diamond recovery through froth separation is their surface hydrophilization by hypergene minerals and technogenic films, crystallized from the supersaturated aqueous phase, fixed on the surface structurally or by adhesion. Various types of physical actions, including thermal and ultrasonic treatment of the initial feed of froth separation, are recommended to increase the diamond-bearing kimberlite beneficiation process performance, providing cleaning of the surface of diamonds due to destruction of their accretions with rock minerals and removal of film hydrophilizing coatings from the surface of diamond crystals. A sample of kimberlite material with a given content of diamonds of 1.5–2 mm in size was used as a subject of research in the process of froth separation. The results of thermodynamic calculations and experimental research have substantiated the necessity of using electrochemical conditioning of recycled water for increasing the efficiency of diamond surface cleaning in froth separation operation when using the process of thermal treatment of initial ore feed. The use of diaphragmless electrochemical conditioning of recycled water increases the efficiency of thermochemical dissolution of hydrophilizing compounds on the surface of diamonds through reducing the concentration of calcium and carbonate ions as well as through shifting the medium pH to 6.1–6.5. The measurements of the limiting wetting angle showed that the maximum effect of increasing the diamond surface hydrophobicity was achieved when heat and electrochemical treatment were used together. Laboratory studies showed the possibility of increasing flotation diamond extraction from 65.7 to 91.4 % through application of electrochemical conditioning of recycled water. The optimum parameters of diaphragmless electrochemical treatment of recycled water of the froth separation cycle in conditions of application of pulp heat treatment: current density of 175–200 A/m2 and power consumption of 1.2–1.5 kWh/m3. Tests carried out at processing plant No. 3 of the Mirny GOK (Mining and Processing Complex) (Mirny, Yakutiya) showed that the application of the developed froth separation process intensification method with the use of thermal treatment of pulp and electrochemical diaphragmless treatment of recycled water allowed increasing the recovery of diamonds of +0.5–2 mm size by 4.9–5.1 %.